How strong is the correlation between unemployment and growth really? The persistence of Okun's Law and how to weaken it - Stefan Marth (WWWforEurope, 2015)
We examine Okun's Law on the basis of new growth perspectives and in the context of the WWWForEurope project. By comparing Okun's work from 1962 with the latest IMF and OECD surveys, a connection is set up and Okun's theoretical framework is updated and its persistence is examined. In addition, the implicit logic of Okun's Law is expressed and stressed, and literature is reviewed from this point of view as well. Furthermore, the main implicit component of Okun's Law - productivity - is taken into account when discussing its breakdown in the WWWForEurope context. After applying the "Difference method", we derive the conclusion that the Okun coefficients and intercepts vary substantially between countries.
Keywords: JO3; JP28; JB2; JB4; JH2; 330; Okun's law; heterogeneity; technological progress; labour market interventions